Methodology for investigating competency index of Technical Vocational Education and Training (TVET) instructors for 4.0 industrial revolution - Shahron, Nuraini; Minghat, Asnul Dahar; Mustakim, Siti Salina (Bumi Publikasi Nusantara, 2022)
The purpose of this study is to construct several methods for evaluating the competency index of Technical Vocational Education and Training (TVET) instructors toward IR4.0. Research methodology is important so that the research conducted has the most appropriate and effective method in answering research problems. Therefore, the research method that is designed involves the interview protocols, the research design, research subject or sample, research procedure, data collection procedure, and data analysis procedure.